Development of the Pertamina pinky movement program through the design thinking approach - Meidina Arimbi Rushartami; Joyo Winoto; Suprehatin Suprehatin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Implementing Social and Environmental Responsibility (TJSL) is an obligation for State-Owned Enterprises (BUMN). To increase value for the Company, implementing TJSL should be carried out with the Company's business approach. Pertamina, one of the BUMNs, is implementing the TJSL program with this approach through the pinky movement program. This program is a funding and business development program for Micro, Small, and Medium Enterprises actors with the primary objective of switching from the use of subsidized LPG to non-subsidized LPG, which is right on target and provides access to the marketing of non-subsidized LPG for the community. This program has been running since 2020, but program development is still needed so that the conversion of subsidized LPG to non-subsidized LPG is optimal. This study aims to formulate a strategy for developing the Pinky Movement program. The research method used qualitative methods for data collection to formulate strategies using design thinking methods. The results at the final stage state that the proposed program development is feasible to run to optimize the program.